Raised Vaginal Fluid Fibronectin Level Indicates Premature Rupture of Membrane (Journal of Enam Medical College, 2012)
Background: Premature rupture of membrane (PROM) is one of the common complications  of pregnancy that has major impact on fetal and neonatal outcome. It is the commonest  clinical event where a normal pregnancy becomes suddenly a high-risk one for mother and  fetus or neonate. Objective: The study was undertaken to investigate whether raised  fibronectin level in vaginal fluid may indicate premature rupture of membrane. Materials and  Methods: This cross sectional study was conducted in the department of Obstetrics and  Gynecology in Sir Salimullah Medical College & Mitford Hospital, Dhaka during the period  of January 2006 to December 2007. A total of 114 pregnant women with gestational age 28th  week up to 40th week were included. Sixty were PROM (Group I) and 54 were non-PROM  (Group II) subjects. Fibronectin in vaginal fluid was measured by an immunochemical  reaction by nephelometer. Statistical analysis was done by SPSS version 10.0. Results: The  PROM patients had significantly higher concentration of fibronectin (225.77 ± 115.18 ng/mL)  compared to that in non-PROM subjects (8.04 ± 16.17 ng/mL) (p < 0.001). Conclusion: It  can be concluded that in cases of unequivocal rupture or intactness of the membranes, the  result of the fibronectin test corresponds well with the clinical situation. So fibronectin is a  sensitive test for detection of amniotic fluid in the vagina. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12841 J Enam Med Col 2012; 2(2): 74-79